Visual-Based Educational Intervention and Token Economy: Enhancing Social–Sexual Awareness in a Child with Down Syndrome - Sekarayu Puspita Sari; Muhammad Nurrifqi Fuadi; Yuli Fajar Susetyo (Faculty of Psychology, Universitas Gadjah Mada, 2026)
Children with Down syndrome have cognitive limitations that affect their ability to understand social norms, including those related to sexual behavior. As they enter puberty, they begin to show sexual interest but often have no understanding of the social context, which can put them at risk of displaying inappropriate sexual behaviors. This study aimed to examine the role of a visual-based educational intervention and the token economy system in enhancing social–sexual awareness in a child with Down syndrome. It employed a quasi-experimental single-subject research design (SSRD) with an A–B type approach. The results indicate a significant reduction in inappropriate sexual behavior, facilitated by the active involvement of both teachers and parents. The use of positive reinforcement-based interventions improving the social–sexual awareness of a child with Down syndrome. These findings suggest that the intervention can be implemented as a social–sexual education strategy by teachers and parents and may serve as an evidence-based alternative intervention in Indonesia.